2009
DOI: 10.1038/hr.2009.110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin II receptor blockers on dementia

Abstract: The renin-angiotensin system (RAS) is involved in pathological mechanisms of target organ damage as well as the induction of hypertension; therefore, blockade of the RAS has been expected to prevent cardiovascular and cerebrovascular diseases beyond its antihypertensive effects. In spite of the well-characterized role of angiotensin (Ang) II receptor blockers (ARBs) in preventing the onset and recurrence of stroke, the clinical evidence for an effect of ARBs on dementia has not been definitive. However, prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 34 publications
3
27
0
1
Order By: Relevance
“…[16][17][18][19][20][21] In addition, as angiotensin-converting enzyme inhibitors, angiotensin receptor blockers and potassium sparing diuretics have an advantage in preventing CI, activation of the renin-angiotensin system or low potassium concentration has been suggested to be involved in CI through possible contributors to CI pathogenesis, including oxidative stress, inflammation, platelet aggregation and vasoconstriction. [22][23][24][25][26][27][28][29] Aldosterone, a crucial factor downstream of the renin-angiotensinaldosterone system, has also been shown to cause target organ damage independent of its effects on blood pressure and to be a potent cerebrovascular risk factor. In this study, we showed that increased PAC is associated with CI.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21] In addition, as angiotensin-converting enzyme inhibitors, angiotensin receptor blockers and potassium sparing diuretics have an advantage in preventing CI, activation of the renin-angiotensin system or low potassium concentration has been suggested to be involved in CI through possible contributors to CI pathogenesis, including oxidative stress, inflammation, platelet aggregation and vasoconstriction. [22][23][24][25][26][27][28][29] Aldosterone, a crucial factor downstream of the renin-angiotensinaldosterone system, has also been shown to cause target organ damage independent of its effects on blood pressure and to be a potent cerebrovascular risk factor. In this study, we showed that increased PAC is associated with CI.…”
Section: Discussionmentioning
confidence: 99%
“…It is also suggested that AT1 blockers may have neuroprotective effects, reducing the incidence of stroke and improving cognition function. 85,86 In addition, renal afferent nerves may also contribute to the blood pressure elevation according to the recent findings of the renal nerve ablation in patients with resistant hypertension. 8,10 Renal afferent nerves project directly to many areas in the central nervous system controlling the sympathetic nervous system activity such as the NTS and hypothalamus.…”
Section: Effects Of At1 Receptor Blockers On Oxidative Stress In the mentioning
confidence: 99%
“…25 Kume et al 26 demonstrated that telmisartan improved cognitive function in Alzheimer's disease patients with hypertension more than amlodipine, although the difference was not significant, whereas Imabayashi et al 27 found that it controlled declining glucose metabolism in the olfactory tract of patients with Alzheimer's disease. The present study did not undertake a detailed investigation of cognitive and other higherorder brain functions.…”
Section: Discussionmentioning
confidence: 99%